2010
DOI: 10.1063/1.3327839
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and spectroscopy of vibrational overtone excited glyoxylic acid and 2,2-dihydroxyacetic acid in the gas-phase

Abstract: The early time dynamics of vibrationally excited glyoxylic acid and of its monohydrate 2,2-dihydroxyacetic acid are investigated by theoretical and spectroscopic methods. A combination of "on-the-fly" dynamical simulations and cavity ring-down spectroscopy on the excited O-H stretching vibrational levels of these molecules observed that conformers that possess the correct structure and orientation react upon excitation of Deltaupsilon(OH)=4,5, while the structurally different but near isoenergetic conformers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 123 publications
2
50
0
1
Order By: Relevance
“…A comparison of the B3LYP energies to the more accurate CCSD(T) results (shown in parentheses in Table I) suggest that the B3LYP results are expected to have errors on the order of several kcal/mol. This level of accuracy is consistent with our previous studies of intramolecularly hydrogen-bonded systems such as glycolic acid, 53 pyruvic acid, 54, 55 glyoxylic acid, 56,57 and fluoromethanol. 30,31 For the purpose of comparing dynamical simulation to statistical theory, we have also located and characterized the transition state structures.…”
Section: Quantum Chemistry Methodology: Reactive Dynamics Simulatsupporting
confidence: 92%
“…A comparison of the B3LYP energies to the more accurate CCSD(T) results (shown in parentheses in Table I) suggest that the B3LYP results are expected to have errors on the order of several kcal/mol. This level of accuracy is consistent with our previous studies of intramolecularly hydrogen-bonded systems such as glycolic acid, 53 pyruvic acid, 54, 55 glyoxylic acid, 56,57 and fluoromethanol. 30,31 For the purpose of comparing dynamical simulation to statistical theory, we have also located and characterized the transition state structures.…”
Section: Quantum Chemistry Methodology: Reactive Dynamics Simulatsupporting
confidence: 92%
“… 34 They also showed that vibrational overtone excitation of the O–H mode with four or five vibrational quanta leads to decomposition of glyoxylic acid if the hydrogen atom is oriented to form an intramolecular hydrogen bond. 35 The isomerization reactions involved in formation of this intramolecular hydrogen bond can be induced by near-infrared light, as shown in argon matrices by Olbert-Majkut et al 36 In aqueous solution, Guzman and co-workers identified a number of photolysis products, including CO 2 , CO, formic acid, oxalic acid, and tartaric acid. 25 They propose the homolytic cleavage of the C–C bond as the first step in the reaction cascade, followed by a series of bimolecular reactions.…”
Section: Introductionmentioning
confidence: 98%
“…71,72 Light-initiated ground electronic state reactions of this type can initiate endothermic reactions and induce photochemistry in acids and alcohols which have electronic states too high in energy to undergo atmospheric excited electronic state photochemistry. 7,71,72,[75][76][77][78] Water can potentially modify the rates of unimolecular light-initiated reactions on the ground electronic state. This possibility was suggested based on quantum computations of barrier heights by Staikova and Donaldson for vibrational overtone initiated reactions.…”
Section: Role Of Water In Sunlight Driven Reactionsmentioning
confidence: 99%